Liquid Anion Exchange Chromatographic Extraction and Separation of Platinum(IV) with n-Octylaniline as a Metallurgical Reagent: Analysis of Real Samples - Ashwini P. Gaikwad; Ganesh S. Kamble; Sanjay S. Kolekar; Mansing A. Anuse (Journal of Chemistry, 2013)
A simple and selective method was developed for the determination of platinum(IV) with n-octylaniline in toluene. In present study, the use of n-octylaniline in toluene for the extraction of platinum(IV) from ascorbate media was carried out. The effect of various parameters, such as pH, equilibrium time, extractant concentration, and organic solvent on the extraction has been discussed. The back extraction of platinum(IV) has been performed. On the basis of slope analysis, the composition of the extracted species was determined as [RR′NH2+ Pt(Succinate)2−](org). The interfering effects of various cations and anions were also studied, and the selectivity of the method is enhanced by using suitable masking agents. The proposed method is rapid, reproducible and successfully applied for the determination of platinum(IV) in binary and synthetic mixtures. The separation of pt(IV) from other associated metals has been studied. Comparison of the results with those obtained using an atomic absorption spectrophotometer also tested the validity of the method.